If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(x + 5) + -5 = -15 Reorder the terms: -2(5 + x) + -5 = -15 (5 * -2 + x * -2) + -5 = -15 (-10 + -2x) + -5 = -15 Reorder the terms: -10 + -5 + -2x = -15 Combine like terms: -10 + -5 = -15 -15 + -2x = -15 Add '15' to each side of the equation. -15 + 15 + -2x = -15 + 15 Combine like terms: -15 + 15 = 0 0 + -2x = -15 + 15 -2x = -15 + 15 Combine like terms: -15 + 15 = 0 -2x = 0 Solving -2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-2'. x = 0 Simplifying x = 0
| 3p+2(0.5p)=120 | | 6(7x-1)+5=24+3x | | 2c-7=15 | | y+2=-1+6 | | 8t+3=45 | | 77-5x=31x+21 | | -68=17y | | 6x^2+48x+96= | | 12-10x=84-31x | | 4p+7p= | | 5x^2+24x-5=0 | | 22x+8-26x=4-8 | | 4(a)+1-a=1919 | | 6(7x-1)+5=24+x | | k-5=-42 | | -14-3x=14-7x | | 10+k=4k | | y=230x-190 | | 10z^2+6=8 | | x^2+11x=210 | | 100-2x=80 | | 3(x+5)=(3x+15) | | 20-x=3(x+6) | | 6x+33=14x-55 | | 8f-5=-7 | | x-(-7)=15 | | X^2-8x=-16 | | y=-0.02x-0.03 | | (x-1)-(2x-3)=0 | | 2x+14=-31-7x | | -(3x+2y-1)= | | 24x^2-23x-5=0 |